2020
DOI: 10.3390/cancers12020506
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variants in Phosphodiesterase Genes and Genetic Predisposition to Pediatric Adrenocortical Tumors

Abstract: Phosphodiesterases (PDEs) form a superfamily of enzymes that catalyze the hydrolysis of cyclic nucleotides adenosine 3′5′-cyclic monophosphate (cAMP) and guanosine 3′5′-cyclic monophosphate (cGMP) to their inactive 5′ monophosphates. cAMP plays a critical role as a second messenger in endocrine tissues, and activation of cAMP signaling has been reported in endocrine tumors. Germline variants in PDEs have been associated with benign cortisol-secreting adrenocortical adenomas and testicular germ cell cancer but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐seven studies 2,5,16–19,23,24,26,29–34,36–41,43,45,46,48,51 assessed the outcomes between these two groups, and being affected by Cushing syndrome resulted in a worse outcome ( P < .0001; RR 1.88; 95% CI 1.38‐2.58; I 2 6%). Secondly, 19 studies 5,18,20,26,30–33,36–38,40,41,43,45,46,49,51 compared the secreting tumors and nonsecreting masses, identifying hormonal secretion as a negative prognostic factor ( P = .004; RR 1.63; 95% CI 1.17‐2.27; I 2 0%). Finally, the comparison between patients affected by Cushing syndrome and nonsecreting tumors was performed in 17 studies 5,18,20,26,30–33,37,38,40,41,43,45,46,49,51 and no difference in outcome was found ( P = .40; RR 1.19; 95% CI 0.79‐1.79; I 2 0%) (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cGMP performs crucial roles in cell proliferation, differentiation, and apoptosis via intracellular cGMP signaling [58,59] and regulates diverse physiological functions covering platelet aggregation [60], neurotransmission [61], and vascular smoothmuscle modulation [62]. Several studies have been reported that dysregulation of PDE activities is associated with diverse tumors and carcinomas like chronic lymphocytic leukemia, glioblastoma, prostate cancer, breast cancer, adrenocortical tumor, etc [24,63,64]. However, the distinct role of PDE9A in CRC is yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation and expression of PDEs (cyclic nucleotide phosphodiesterases) play a signi cant role in tumor progression and inhibition [23]. Many hematological malignancies and carcinomas have been connected with decreased levels of cAMP and/or cGMP by the PDE gene family [24]. PDE2A, PDE8B, and PDE11A expression are involved with adrenocortical tumors [25], high expression of PDE4 has been detected in brain tumors [26], in glioblastoma multiforme PDE5 is strongly expressed [27], and increased PDE7B expression found in Chronic lymphocytic leukemia [28].…”
Section: Introductionmentioning
confidence: 99%